QUALITY-BASED TRAINING EVALUATION AT BIO FARMA: KIRKPATRICK LEVELS 1–3 - Nadiya Yusriyyah; Wa Ode Zusnita Muizu (UPT Publikasi Ilmiah UNISBA, 2026)
Quality-based training is a critical component in the pharmaceutical industry, where strict regulatory standards require employees to consistently comply with established procedures. However, training effectiveness is often assessed only based on participation and knowledge improvement, without adequately measuring its impact on workplace behavior. Therefore, this study aims to analyze the effectiveness of quality-based training at PT Bio Farma (Persero) using the Kirkpatrick evaluation model at Levels 1–3, namely reaction, learning, and behavior. This research employs a quantitative descriptive approach using secondary data derived from the Quality Training Effectiveness Report for the third quarter of 2025, supported by relevant literature. The analysis covers 44 internal training programs categorized into document, Good Manufacturing Practice, and knowledge training. The results indicate that most training programs are effective, with average scores above the company standard at Levels 1 and 2, reflecting positive participant responses and increased understanding. Level 3 shows a generally high level of behavioral application, although several programs demonstrate less optimal behavioral outcomes. These findings suggest that while training has been effectively implemented, strengthening post-training support is necessary to ensure consistent behavioral change and long-term organizational impact.